1997
DOI: 10.1016/s0022-5347(01)64240-x
|View full text |Cite
|
Sign up to set email alerts
|

Disease Recurrence and Progression in Untreated Pathologic Stage T3 Prostate Cancer: Selecting the Patient for Adjuvant Therapy

Abstract: The majority of patients with pT3 prostate cancer will not experience recurrent disease for many years if ever. Immediate use of adjuvant treatment should be reserved for those patients with a high risk of recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 19 publications
2
34
0
6
Order By: Relevance
“…Similar to previous reports, we did not observe a higher risk for disease recurrence if multiple positive margins were present (1,14). In contrast, Lowe and Lieberman reported that the number of positive margins had an important impact on disease recurrence (15).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous reports, we did not observe a higher risk for disease recurrence if multiple positive margins were present (1,14). In contrast, Lowe and Lieberman reported that the number of positive margins had an important impact on disease recurrence (15).…”
Section: Discussionsupporting
confidence: 90%
“…14, 15 Lowe et al found that men with more than one positive margins were at increased risk of recurrence in univariate analysis. 14 However, no multivariate analysis was performed. In the current study, the number of positive margins remained a significant predictor of recurrence on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, (66,77) patients with multiple margins had a higher risk of failure (44%,27%) than those with a s i n g l e m a r g i n ( 2 1 % , 1 5 % ) . O t h e r s t u d i e s h a v e r eported similar findings (30,53,67), although it is not always an independent predictive factor on multivariate analysis.…”
Section: Which Probably Acc O U N T S F O R S O M E O F T H E V a Rmentioning
confidence: 99%